RNA Interference (RNAi) for plants - Nur Afiqah Md Samad, Nur Afiqah Md Samad; Nur Hanis Abdul Rahim, Nur Hanis Abdul Rahim; Mariam Firdhaus binti Mad Nordin*, Mariam Firdhaus binti Mad Nordin*; Angzzas Sari binti Mohd Kassim, Angzzas Sari binti Mohd Kassim (Penerbit UTHM, 2022)
As we are facing global population development, strategies are required to improve agricultural production in the battle against hunger and poverty. Agricultural biotechnology provides a powerful method in combination of conventional breeding, new innovations and enhanced management of resources which improves the productivity of livestock, aquaculture, and crops. After the finding of RNA interference (RNAi), researchers have made considerable growth in improving this remarkable crop especially in defence technology. RNA interference is a vital plant growth, development and reaction regulator to various types of stresses. This technology leads to higher efficiency and potency of gene silencing, thus becoming the highly promising technology for crop improvements at a rapid rate with some advantages. Nowadays, RNAi has been widely used for the improvement in agricultural biotechnology and seems to be applicable and commercialized in other fields too.